Webinar: Alternative Medicine For Disease Trought Hijamah (Bekam) - Yuyun Bewelli Fahmi; Andriana Andriana (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Data from the Ministry of Health of the Republic of Indonesia, the number of COVID-19 cases is still quite alarming. The pandemic period causes people's life activities to be completely limited and people become worried if they have to go to the hospital, alternative methods are needed to increase immunity in preventing/treating disease. Therefore, this community service aims to educate the public to remain calm and can improve health insight during the pandemic. The method used to provide education to students is to hold webinars through the Zoom teleconferencing application. The material given in this activity is Alternative Medicine for Disease Trought Hijamah (Cupping). In this activity, the participants who attended were 90 participants from housewives, lecturers, students, and private employees with an age range of 18-60 years. The results of the webinar activity show that the level of understanding of participants about COVID-19 is good with an average understanding percentage of 80%, participant interest in Alternative Medicine for Disease Trought Hijamah (Cupping) is good at 75%, and participants are also satisfied with the webinar that has been held (83,3%). From these results, it was concluded that participants who had participated in this activity were able to understand about the COVID-19 disease and were interested in alternative medicine in preventing/treating disease.